What are the most essential social-emotional skills?: Relationships between adolescents’ social-emotional skills and psychosocial health variables: an explorative cross-sectional study of a sample of students in preparatory vocational secondary education - Van De Sande, Marion Cornelia; Leonardus Kocken, Paul; Diekstra, Rene Folquinus; Reis, Ria; Gravesteijn, Carolien; Fekkes, Minne (Frontiers in Education, 2023)
Universal school-based social-emotional learning (SEL) programs target several social-emotional skills assuming a relationship between the skills and psychosocial health outcomes. However, greater insight into the relationship is required to clarify the skills that are most crucial to address. It will support the development and refinement of SEL programs. This study investigated 1) the relationship among the social-emotional skills, 2) the association between the skills and psychosocial health variables, and 3) the mediating effect of the skills on psychosocial variables. Using self-report questionnaires (N = 796) completed by adolescent students (aged 14-18) in preparatory vocational tracks in Dutch secondary education, associations were identified between five SEL skills and two psychosocial health variables, emotional-behavioral difficulties, and prosocial behavior. There was a high degree of overlap between the five skills (self-awareness, social awareness, self-management, relationship skills, and responsible decision-making). The skills were univariately associated with emotional-behavioral difficulties and prosocial behavior. In the multivariate model, self-management most strongly correlated with emotional-behavioral difficulties and mediated the relationship between self-awareness and emotional-behavioral difficulties. Social awareness showed the highest correlation with prosocial behavior and mediated the relationship between prosocial behavior and three other skills: self-awareness, relationship skills, and responsible decision-making. Self-management and social awareness seem to be the central skills to promote the psychosocial health outcomes of students in preparatory vocational secondary education tracks. These two skills mediate the relationship between other social-emotional skills, emotional-behavioral difficulties, and prosocial behavior.